Design and analysis of frequency division phase-coded waveforms for MIMO over-the-horizon radars - Hong, Sheng; Yan, Maosong; Wang, Yuhao; Ai, Yu; Dong, Yantao; Zhao, Zhixin (Journal of applied remote sensing, 2018)
This paper addresses the optimization problem of frequency division phase-coded (FDPC) waveforms for improving the detection performance in multiple-input multiple-output over-the-horizon radars (MIMO-OTHR). A sparse frequency division complementary chaotic modulation (SFDCCM) waveform is proposed and analyzed. First, the basic structure of the FDPC waveform is presented, and its MIMO ambiguity function is derived to provide guidance on further waveform optimization. It turns out that the modulation codes and carrier frequencies are two key factors for good waveform performance. Then, the chaotic sequences are introduced due to their unique advantages, and an adaptive clonal selection algorithm is utilized to obtain a pair of complementary chaotic sequences to suppress the range sidelobes. The optimized complementary pair is modulated on different carrier frequencies. As the available spectrum of the MIMO-OTHR is discontinuously distributed, the carrier frequencies are generally sparse and should be properly selected according to the real-time frequency spectrum monitoring (RTFSM) system. Finally, the SFDCCM is proposed based on the FDPC structure. The pulse compression results of the SFDCCM are compared with typical waveforms. Four cases of carrier frequency selection in the SFDCCM and the corresponding doppler tolerance are analyzed. Simulation results validate the superiority of the proposed waveform in this paper.